Rare Case Report: Guillain–Barré Syndrome As A Neurological Complication In Patients With Dengue Fever - R Zhafira Arrum Prabapatitis; Muhammad Adam Prabasunu (Jurnal Sehat Indonesia (JUSINDO), 2026)
Dengue virus infection has many complications, one of the rare neurological complications is Guillain-Barre syndrome (GBS). Dengue virus is classified into four serotypes, namely DENV-1, DEN-2, DEN-3 and DEN-4, while the most frequent causes of neurological complications are DEN-2 and DEN-3. This case report aims to a rare case of Guillain-Barré syndrome as a neurological complication of dengue fever and highlight the importance of early diagnosis and management. Case Reports: A 46-year-old man has had two main complaints of weak limbs, tingling and numbness since the last 5 days, followed by complaints of both weak arms, tingling and numbness since the last 4 days, accompanied by heartburn pain and double vision. The patient had a previous hospitalization history 10 days ago with a diagnosis of dengue fever with a positive NS 1 result. The physical examination found that the lateralized muscle strength of the sinistra and physiological reflexes were reduced in both legs and both arms, pain sensations and palpable sensations were reduced. The results of the examination are in accordance with the results of the ENMG examination, namely the AMSAN type GBS. Currently, patients are diagnosed with GBS as a sequel to dengue fever infection. The pathogenesis of GBS caused by the dengue virus is mediated by the immune system against the DEN serotype that affects peripheral nerves. Based on previous case reports, GBS cases are one of the neurological complications of dengue fever. GBS is one of the neurological complications in patients with dengue fever.